Multicultural Leadership in School Administrators in International School in Chiang Mai - Seadsophonkul, Anawat; Wangcham, Sangwan (MCU Haripunchai Review, 2026)
This research aimed to study 1) multicultural leadership in school administrators and 2) guidelines for developing multicultural leadership among school administrators in international schools in Chiang Mai Province. The research design was mixed-methods. The population and sample consisted of 164 school administrators and teachers, and 5 informants were interviewed. The research instruments used were questionnaires with a reliability coefficient of 0.93 and interview forms. Statistics used for data analysis included percentages, means, and standard deviations, and content analysis, presented descriptively The results revealed: 1) Multicultural Leadership in School Administrators in International School in Chiang Mai Overall, the results were found to be at a high level, including acceptance of cultural diversity, ethical conduct, communication skills, and resource support. 2) Development guidelines Multicultural Leadership in School Administrators in International School in Chiang Mai It was found that administrators should promote understanding and cooperation within the organization, as well as support the adaptation and learning of Thai culture for foreign teachers. Administrators should use local languages ​​to build understanding and good relationships between the educational institution and the community. Administrators should allocate appropriate budgets and resources to support multicultural activities and consider the importance of activities in building cultural understanding and integration. Educational institution administrators should promote open exchange of ideas and build diverse teams to ensure careful and transparent decision-making.